Cybersastra: Kontributifkah untuk Meningkatkan Literasi Sastra di Tengah Budaya Digital? - Lenie Nuraeni Pujayantie; Yeti Mulyati; S. Sumiyadi; Halimah Halimah (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
The rapid development of digital culture, characterized by instant access to information, has fostered an "instant culture" that significantly impacts literacy practices, particularly literary literacy. This phenomenon raises concerns about declining interest in conventional literary works. However, amid these challenges, cyber literature (cybersastra) emerges as an adaptive form of literature in digital spaces, offering potential solutions to enhance literary literacy. This study aims to examine the role of cybersastra in improving literary literacy amid the increasingly dominant digital culture. Using a descriptive qualitative approach, data were collected through questionnaires distributed to students, university students, and teachers active in digital environments. The instrument was disseminated via Google Forms and analyzed using thematic descriptive techniques, including frequency and percentage tabulation, followed by narrative interpretation to uncover patterns and meanings within the responses. The results reveal that instant culture has changed how people access and consume information, yet cybersastra has proven to be an appealing and accessible alternative form of literacy aligned with the digital habits of the current generation. Respondents acknowledged that cybersastra enhances reading interest and is relevant for educational purposes, provided it is accompanied by proper guidance. This study concludes that cybersastra not only broadens the concept of literacy but also offers an adaptive and meaningful approach to literary education in the digital era.